(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the status of sleep quality of medical student at University of Medicine and Pharmacy – Vietnam National University studied at Hoa Lac in 2022-2023. Subject and method: A cross - sectional study was carried out among 422 students on the first year in University of Medicine and Pharmacy - Vietnam National University studied at Hoa Lac in 2022-2023. Results: The percentage of poor sleep quality according to the PSQI scale accounted for 36,5% (PSQI > 5). Conclusion: Sleep quality of medical students are not good, there should be improvements in students’ knowledge about the importance of sleep as well as sharing from families and universities to reduce studying and social pressure among students.